2022
DOI: 10.3390/su14148822
|View full text |Cite
|
Sign up to set email alerts
|

Role of Education, Training, and E-Learning in Sustainable Employment Generation and Social Empowerment in Saudi Arabia

Abstract: This study analyzes the role of education, training, and e-learning (ETL) in empowering Saudi society, leading to sustainable employment generation in Saudi Arabia. It applies the theory of constructivism, scoping to human aspects of teaching and learning in sustainable employment generation and social empowerment. The study primarily collects the existing variable pools from the available literature on education (EDU), training (TRA), e-learning (ELRN), government policies (GPOL), national culture (NCUL), sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 115 publications
1
25
0
Order By: Relevance
“…For both domestic and international issues on factors affecting employment, international scholars have analyzed the impact of employment from different perspectives and using different measures.Bhorat (2016) [1] estimated Olley and Pakes' two-stage regression of the modified Cobb-Douglas production function to analyze the extent to which labor force education affects the nature and trajectory of South Africa's economic growth. The results show that the degree queue contributes to economic growth and employment; Singh (2022) [2] conducted second-order partial least squares structural equation modeling (PLS-SEM) through mitigation analysis and found that learners would be able to maintain their experience by connecting with the outside world and building a sustainable society, thus creating sustainable employment opportunities and social empowerment in Saudi Arabia; Zhang Chewei (2019) [3] analyzed from the macro and micro aspects and pointed out that the main contradiction of employment in China has gradually changed from the total contradiction characterized by lack of employment positions to the structural contradiction characterized by low employment quality. The improvement of the wage level and employment quality of ordinary workers has become an important issue to be solved.…”
Section: Literature Reviewmentioning
confidence: 98%
“…For both domestic and international issues on factors affecting employment, international scholars have analyzed the impact of employment from different perspectives and using different measures.Bhorat (2016) [1] estimated Olley and Pakes' two-stage regression of the modified Cobb-Douglas production function to analyze the extent to which labor force education affects the nature and trajectory of South Africa's economic growth. The results show that the degree queue contributes to economic growth and employment; Singh (2022) [2] conducted second-order partial least squares structural equation modeling (PLS-SEM) through mitigation analysis and found that learners would be able to maintain their experience by connecting with the outside world and building a sustainable society, thus creating sustainable employment opportunities and social empowerment in Saudi Arabia; Zhang Chewei (2019) [3] analyzed from the macro and micro aspects and pointed out that the main contradiction of employment in China has gradually changed from the total contradiction characterized by lack of employment positions to the structural contradiction characterized by low employment quality. The improvement of the wage level and employment quality of ordinary workers has become an important issue to be solved.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The Job Characteristics Model (JCM) posits that job design plays a crucial role in enhancing satisfaction ( Hackman and Oldham, 1975 ), particularly relevant under the ongoing educational reforms in Saudi Arabia ( Singh et al, 2022 ). This perspective aligns with Self-Determination Theory (SDT), which identifies autonomy, competence, and relatedness as fundamental to faculty well-being ( Deci and Ryan, 2012 ; Haw et al, 2023 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the impetus behind scientific inquiry, which is crucial for the progress of a nation, influences its ability to compete in the global knowledge-based economy ( Alsharari, 2020 ). Hence, the significance of upholding academic progress in Saudi Arabia cannot be overstated, as it plays a crucial role in achieving the needed advancements across diverse sectors, aligning with the aspirations outlined in Vision 2030 ( Singh et al, 2022 ). Hence, it is imperative to establish conducive work environments within Saudi higher education institutions in order to effectively retain faculty members, enhance their job motivation, and assist them in navigating various challenges ( Kuwaiti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, additional research is required to determine the role of educational technology in developing university students' cognitive and communication skills. This is especially true for Saudi Arabia, as it has been investing tremendous resources to develop its higher education sector (Singh et al, 2022a;2022b;Alam et al, 2022…”
Section: *Educationalmentioning
confidence: 99%